2015
DOI: 10.1371/journal.pone.0130148
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Lymph Node Pathology; Fine Needle Aspiration Biopsy as an Evaluation Tool for Lymphadenopathy: A Retrospective Descriptive Study Conducted at the Largest Hospital in Africa

Abstract: BackgroundLymphadenopathy is a common clinical presentation of disease in South Africa (SA), particularly in the era of Human Immunodeficiency Virus (HIV) and tuberculosis (TB) co-infection.MethodsData from 560 lymph node biopsy reports of specimens from patients older than 12 years at Chris Hani Baragwanath Academic Hospital (CHBAH) between 1 January 2010 and 31 December 2012 was extracted from the National Health Laboratory Service (NHLS), division of Anatomical Pathology. Cytology reports of lymph node fine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…In our study the predominant age group affected with lymphadenopathy were between 5-10 years among children (57%) and 15-30 years among adult (52%) whereas study by Srivatsav showed predominance of lymphadenopathy among 21-50 years (49.11%) followed by 0-20 years (36.98%) [4] . Our study showed females preponderance for lymphadenopathy (60%) especially among adult between 15-30 years of age than male which was supported by other studies where the female predominance observed were 55% and 61% respectively [5,6] . Similar to other studies, cervical lymphadenopathy was a common presentation in our study.…”
Section: Discussionsupporting
confidence: 90%
“…In our study the predominant age group affected with lymphadenopathy were between 5-10 years among children (57%) and 15-30 years among adult (52%) whereas study by Srivatsav showed predominance of lymphadenopathy among 21-50 years (49.11%) followed by 0-20 years (36.98%) [4] . Our study showed females preponderance for lymphadenopathy (60%) especially among adult between 15-30 years of age than male which was supported by other studies where the female predominance observed were 55% and 61% respectively [5,6] . Similar to other studies, cervical lymphadenopathy was a common presentation in our study.…”
Section: Discussionsupporting
confidence: 90%
“…However, Africa has seen an increase in the TB burden [10]. In particular, TB lymphadenitis is the most common extrapulmonary manifestation in developing countries [11].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in diagnosing TB lymphadenitis, FNAB is widely regarded as the diagnostic modality of choice. A study by Reddy et al [10] showed a good correlation between FNAB diagnosis and biopsy diagnosis in lymph node specimens. According to the study, in the event of inadequate FNAB samples, the result should be treated with reserve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, skin biopsies from patients with unrestrained lymphoproliferation as a result of autoimmune lymphoproliferative syndrome show granulomatous pathology. 142 The progression of lymphoid hyperplasia to granulomatous inflammation is also observed in broader patient populations, where granulomatous inflammation was found in 22% of lymph node fine needle aspirations done to evaluate lymphadenopathy 143 as well as 20 of 38 biopsies for mediastinal lymphadenopathy in patients without CVID or known primary immune dysregulation disorder. 144 …”
Section: Interstitial Lung Diseasementioning
confidence: 99%